(untitled) (Research, Society and Development, 2022)
Objective: mapping of the distribution of Aedes spp. in the urban area of the municipality of Picos, Piauí associating the climate variables and identification the dengue virus serotypes circulating in Aedes aegypti mosquito populations. Methods: Thirty larvitraps were installed in 10 neighborhoods in the urban area of the municipality. Larvae were collected weekly during the period from February 2017 to July 2019, and the collected material was taken to laboratory for identification and counting. The number of larvae were associated with meteorological data. In adult stage, the A. aegypti mosquitoes were segregated into pools containing six specimens and were then subjected to RT-PCR and Nested-PCR assay for detection of the DENV serotype. Results: a total of 44,798 Aedes spp. larvae were collected in the urban area of Picos during study period. An increase in precipitation and decrease in temperature in the months of February and March contributed to the increase in infestation of these vectors in April. In the study, two larvae of Haemagogus spegazzinii, a potential vector of yellow fever, were collected. The highest occurrence in the municipality was of the species A. aegypti (96.43%) present in all neighborhoods studied with predominance in domiciliary environment, while A. albopictus (3.57%) occur in the peridomiciliary environment. Molecular analyzes of the A. aegypti were positive for DENV 1 and DENV 3 viruses, demonstrating the existence of transovarial transmission. Conclusion: This study showed the simultaneous occurrence of A. aegypti and A. albopictus in the urban area and the co-circulation of dengue serotypes 1 and 3. Entomological and viral circulation monitoring are important tools to indicate areas of greater infestation of vector mosquitoes and prevent future outbreaks, providing results for the actions aimed at the control and prevention of arboviruses, through the secretary of health and competent bodies in the region.